The Effect of CaCl2 Added PRP (Platelet Rich Plasma) to the Healing Time, Tensile Strength and Adhesion Degree of the Ruptured Tendinopathic Achilles Tendon of Rats (Rattus norvegicus) - Istan Irmansyah Irsan; R. Muhammad David Jayanegara (Fakultas Kedokteran Universitas Lambung Mangkurat, 2019)
Abstract: Achilles tendinopathy produce morbidity, long-lasting disability in athletes and non-athletes and remain a challenge for clinician. Tendinopathy may lead to reduced tensile strength and a predisposition to rupture.The aim of our study was to evaluate the effects of activated and non-activated PRP on the healing process of ruptured tendinopathic achilles tendon in rat. Tendinopathy achilles condition induced by injecting collagenase bacterial type-1 locally. Right achilles tendon in 48 rats ruptured by transecting it transversely and repaired it by using a Kessler technique. Further, the wound immobilized with PRP and injecting activated PRP (5% CaCl2 added) in one group, non-activated PRP on the other group and saline on control group. Tendons from each group were collected at the 1st and 2nd week postoperatively also assessed for biomechanical test. Tendons were also evaluated histologically by using hematoxylin-eosin to know adhesion degree based on Tang criteria. The significant differences was found between intervention group and control (p<0.05) at the 1st week but there was not any significant differences at the 2nd week in tensile strength test (p>0.05). Adhesion degree of the intervention group also reduce better rather than the control at the 1st and 2nd week (p<0.05). PRP have a positive effect on healing tendons by improving healing time, mechanical strength and decreasing adhesion degree. Keywords: achilles tendinopathy, PRP, healing time, tensile strength, adhesion